2020
DOI: 10.3846/jau.2020.11265
|View full text |Cite
|
Sign up to set email alerts
|

Post-Occupancy Evaluation of Pagerjurang Permanent Housing After the Merapi Volcanic Eruption

Abstract: Merapi Volcano erupted in 2010 and a community-based relocation of the destroyed area was implemented step by step in 2011, 2012, and 2013. This study, therefore, employed the Post-Occupancy Evaluation (POE) Method to investigate the ability of the new (permanent) housing model in Pagerjurang Kepuharjo Village, Yogyakarta to make its residents feel at home more than the old one and to determine the residents’ responses to their life after 10 years of living in the new model. Questionnaires were used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This ensures that the houses are not merely visually pleasing, but also functionally suitable to increase residential satisfaction and overall well-being. Furthermore, in line with multiple studies [11,14,22,26,31,38,59,81,82], the study identified dissatisfaction among resettled households regarding the layout of permanent houses in resettlement. The findings of this study are consistent with previous research conducted by several researchers [23,26,32,59], highlighting that the houses in Panipokhari also overlooked the need for space for addition and modification, a crucial factor for housing satisfaction.…”
Section: Discussionsupporting
confidence: 56%
“…This ensures that the houses are not merely visually pleasing, but also functionally suitable to increase residential satisfaction and overall well-being. Furthermore, in line with multiple studies [11,14,22,26,31,38,59,81,82], the study identified dissatisfaction among resettled households regarding the layout of permanent houses in resettlement. The findings of this study are consistent with previous research conducted by several researchers [23,26,32,59], highlighting that the houses in Panipokhari also overlooked the need for space for addition and modification, a crucial factor for housing satisfaction.…”
Section: Discussionsupporting
confidence: 56%
“…The developed core house can be expanded by repeating a structural frame that is modular and directed by the design to accommodate the development [13]. In the Pagerjurang post-reconstructed housing evaluation, Wulansari (2014) and Setiadi et al ( 2020) studied the interrelation aspects of old and new spaces, the role of government in resettlement efforts and inhabitants' involvement through the social, economic and culture sectors [11] [14].…”
Section: Post-disaster Housing Reconstruction Policymentioning
confidence: 99%
“…As a result, the people of Kepuharjo Village need new settlements. For this reason, Pagerjurang permanent shelter is one of the post-Merapi relocations built by the Government and Rekompak to meet the needs of the victims of the eruption (Setiadi et al, 2020). The sudden movement of people due to the disaster to the Pagerjurang permanent shelter caused the Kepuharjo community to require adjustments to their housing patterns in new settlements.…”
Section: Introductionmentioning
confidence: 99%